1984
DOI: 10.1002/cne.902220304
|View full text |Cite
|
Sign up to set email alerts
|

Organization within the cranial IX–X complex in ranid frogs: A horseradish peroxidase transport study

Abstract: Cranial nerves IX and X in frogs have been described as originating from a nuclear group referred to as the IX-X complex. We studied the central nervous system components of this complex in Rana pipiens and R. catesbiana by labeling peripheral branches of cranial nerves IX and X and identifying the central nervous system contributions of these branches. Various peripheral nerves (IX and the cardiac, gastric, pulmonary, and laryngeal branches of X) were identified and soaked in horseradish peroxidase (HRP). One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
1
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 24 publications
3
37
1
1
Order By: Relevance
“…These involve several nuclei: the para-brachial and Kolliker-Fuse, solitary, dorsal vagus, paratrigeminal (PA5), trigeminal subnucleus caudalis (SC5), raphe magnus, area postrema and medial and lateral reticular nuclei in the medulla oblongata and pons (rostro-ventro-lateral and lateral). The vagus' visceral information is important for maintaining the reflexes conserving homeostatic functions and which are coordinated together with talking, masticatory-deglutitoryrespiratory, pain modulation, cardio-pulmonary, vasopressor, secretomotor and somatomotor mechanism complexes; trigeminal afferents participating in vegetative, gustatory, pneumotaxic and cardio-respiratory centers (Kalia & Mesulman, 1980;Stuesse et al, 1984;Bon et al, 1997;Armstrong & Hopkins, 1998;Saxon & Hopkins, 1998;Ruggiero et al, 2000;Caous et al, 2001;Sato & MomoseSato, 2004;Afifi & Bergman, 2005;Kobayashi et al, 2005). The vagus' afferents mostly reach the solitary nucleus, the rest the vagal dorsal nucleus and PA5 and SC5 nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…These involve several nuclei: the para-brachial and Kolliker-Fuse, solitary, dorsal vagus, paratrigeminal (PA5), trigeminal subnucleus caudalis (SC5), raphe magnus, area postrema and medial and lateral reticular nuclei in the medulla oblongata and pons (rostro-ventro-lateral and lateral). The vagus' visceral information is important for maintaining the reflexes conserving homeostatic functions and which are coordinated together with talking, masticatory-deglutitoryrespiratory, pain modulation, cardio-pulmonary, vasopressor, secretomotor and somatomotor mechanism complexes; trigeminal afferents participating in vegetative, gustatory, pneumotaxic and cardio-respiratory centers (Kalia & Mesulman, 1980;Stuesse et al, 1984;Bon et al, 1997;Armstrong & Hopkins, 1998;Saxon & Hopkins, 1998;Ruggiero et al, 2000;Caous et al, 2001;Sato & MomoseSato, 2004;Afifi & Bergman, 2005;Kobayashi et al, 2005). The vagus' afferents mostly reach the solitary nucleus, the rest the vagal dorsal nucleus and PA5 and SC5 nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…All the 53 neurons (empty circles) depicted were found to distribute at 0.6-2.2 mm rostral to the obex, 0.3-1.2 mm from the midline, and 0.25 to 1.8 mm in depth from the dorsal surface of the medulla. As seen in the figure, all the neurons distribute approximately within the NTS, the region surrounding the tractus solitarius (TS) and its ventromedial portion (OPDAM et al, 1976;HANAMORI and ISHIKO, 1983b;STUESSE et al, 1984). Neurons which responded to both antidromic stimulation of the XIIth nerve and taste stimulation of the tongue existed within the region caudomedial to the NTS.…”
Section: Relationshipmentioning
confidence: 98%
“…Electrophysiological (KUMAI, 1980;IsHIKo, 1981, 1983a;NAKACHI et at., 1985) and histological (HANAMORI and ISHIKO,1983b;STUESSE et al, 1984) studies on frogs have revealed that a majority of chemical information in the frog IXth nerve is transmitted to the nucleus tractus solitarius (NTS) which, in turn, sends it to the hypoglossal motor nucleus (HMN). The glossopharyngeohypoglossal reflex arc thus should contain at least two neuron pools in the lower brain stem, the NTS and HMN.…”
mentioning
confidence: 99%
“…They are situated at the bifurcation of the internal and external carotid arteries and innervated by branches of the glossopharyngeal nerve, which projects its afferent fibres to the NTS in the brainstem (48). These receptors are functionally similar to the mammalian carotid bodies, as they also respond to hypercapnia and their discharge can be modulated by sympathetic stimulation (1).…”
Section: Amphibiansmentioning
confidence: 99%